Conservation Technology Research 2000–2026 Mapping Themes Methods and Application Domains: A Bibliometric Approach - Judijanto, Loso (Westscience Press, 2026)
This study aims to map the intellectual structure, thematic evolution, and application domains of conservation technology research published between 2000 and 2026 using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to examine publication trends, keyword co-occurrence, thematic clustering, and temporal developments. The results reveal that conservation technology research is strongly centered on sustainable development, which acts as the main conceptual hub connecting various domains such as energy transition, environmental protection, water and soil conservation, and ecological monitoring. Cluster analysis indicates that the field is structured around key themes including renewable energy and emission control, environmental remediation, ecosystem conservation, and biological research. The temporal analysis shows a clear shift from traditional ecological studies toward applied technological solutions and, more recently, toward sustainability innovation and energy-focused research. Furthermore, density analysis highlights the dominance of established topics such as sustainability and energy, while also identifying emerging areas such as machine learning and remote sensing as potential future research directions. This study contributes by providing a comprehensive overview of conservation technology research and offers insights into its interdisciplinary nature, evolution, and future opportunities.